CHATGPT IN THE EDUCATIONAL PROCESS OF UKRAINE - Крупко, Олена (SWorldJournal, 2023)
The article provides information on the use of ChatGPT on the territory of Ukraine. The possibilities of the chatbot, as well as its disadvantages and advantages, the consequences of the introduction of artificial intelligence into the educational proces